Other information relevant to the law of the sea - United Nations (Law of the Sea Bulletin, 2013)
Recalling its previous resolutions concerning the situation in Somalia, especially resolutions 1814 (2008), 1816 (2008), 1838 (2008), 1844 (2008), 1846 (2008), 1851 (2008) and 1897 (2009),